Extensive acquired macular hyperpigmentation in a teenager. (1st October 2022) - Tsentemeidou, Aikaterini; Vakirlis, Efstratios; Sideris, Nikolaos; Bobos, Mattheos; Panagopoulou, Angeliki; Ioannides, Dimitrios; Sotiriou, Elena
Abstract: A teenage girl with phototype IV skin presented with extensive gradually progressing asymptomatic macular hyperpigmentation not responding to topical steroids for several months. Histopathology showed foci of increased numbers of melanophages and melanin in the dermis. Click here for the corresponding questions to this CME article.